ANALISIS NILAI TAMBAH PADA RANTAI PASOK KOPI ROBUSTA OLAH KERING DI DESA MUNDUK TEMU, PUPUAN, TABANAN - Satria Nugraha,, I Dewa Gede; Suryawan Wiranatha, A. A. P. Agung; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): MaretDO - 10.24843/JRMA.2019.v07.i01.p08, 2019)
The objective of this research were to determine the supply chain of robusta coffee the added value of each element of the robusta coffee supply chain, and to make alternative policy recommendations to increase the added value of farmers in the Munduk Temu Village, Pupuan, Tabanan. This research was conducted from April to June 2018. This study used a survey method with questionnaire, and used the Hayami method to determine the value added of each element of the supply chain. Alternative recommendations were determined by using the AHP method. There are 3 patterns of robusta coffee supply chain in Munduk Temu, Pupuan, Tabanan : pattern I farmers - processing factories - traders, patterns II farmers - brokers - processing factories - traders, and patterns III farmers - middlemen - collectors - processing factories - traders. The flow goods from farmer and end at the trader, while the money and information flow from traders and end at the farmer. The added value in supply chain pattern I was Rp.4,066/Kg Ose, Rp.4,540/Kg Ose on chain pattern II, and Rp.2,322/Kg Ose for chain pattern III. The value received by each element of the supply chain was Rp.422/Kg Ose for chain I farmers, Rp.446/Kg Ose for chain II farmers and Rp. 451/Kg Ose for chain III, Rp.450/Kg Ose for chain II middleman, Rp.903/Kg Ose for chain III middleman, Rp. 2,944/Kg Ose for processing mills, and Rp.700/Kg Ose for traders. Alternative recommendations for increasing the added value of robusta coffee by using AHP analysis showed that the criteria of post-harvest processing with alternative dry-processing methods and indicators ose coffee were the priorities that play an important role in increasing the added value of robusta coffee at the farm level. Keywords : robusta coffee, supply chain, value-added, Hayami Method.